2002
DOI: 10.1128/aem.68.4.1534-1540.2002
|View full text |Cite
|
Sign up to set email alerts
|

Induction, Isolation, and Characterization of Two Laccases from the White Rot BasidiomyceteCoriolopsis rigida

Abstract: Previous work has shown that the white rot fungus Coriolopsis rigida degraded wheat straw lignin and both the aliphatic and aromatic fractions of crude oil from contaminated soils. To better understand these processes, we studied the enzymatic composition of the ligninolytic system of this fungus. Since laccase was the sole ligninolytic enzyme found, we paid attention to the oxidative capabilities of this enzyme that would allow its participation in the mentioned degradative processes. We purified two laccase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 56 publications
5
86
1
8
Order By: Relevance
“…castanella and L. crinitus laccases from other basidiomycetes presented optimum pH 3.0 using ABTS as substrate (Saparrat et al, 2002;Ryan et al, 2003;Zouari-Mechichi et al, 2006). The present results demonstrated that i) the pH of the culture medium influenced the growth and in vitro decolorization of RBBR by L. crinitus CCB274 and P. castanella CCB444; ii) the fungi were able to alter the initial pH of the medium so that it would reach the optimum pH for growth; iii) RBBR decolorization by these fungi seemed to be the result of the action of laccase-type oxidases.…”
Section: Resultsmentioning
confidence: 99%
“…castanella and L. crinitus laccases from other basidiomycetes presented optimum pH 3.0 using ABTS as substrate (Saparrat et al, 2002;Ryan et al, 2003;Zouari-Mechichi et al, 2006). The present results demonstrated that i) the pH of the culture medium influenced the growth and in vitro decolorization of RBBR by L. crinitus CCB274 and P. castanella CCB444; ii) the fungi were able to alter the initial pH of the medium so that it would reach the optimum pH for growth; iii) RBBR decolorization by these fungi seemed to be the result of the action of laccase-type oxidases.…”
Section: Resultsmentioning
confidence: 99%
“…1B). Copper is a laccase cofactor which presents four cupric ions each associated with one single polypeptide chain (23) but it also has been proved that this element may play an important role in laccase genes regulation at transcription level as showed in Trametes versicolor (7) Phanerochaete chrysosporium (9), Pleurotus ostreatus (18) and Coriolopsis rigida (20). The 250 µM Cu provided the highest laccase activity in LN cultures, which is in accordance to the findings for other fungi, like T. versicolor (400 µM) (7), P. ostreatus (1.0 mM) (3) and V. volvacea (200 µM) (6).…”
Section: Discussionmentioning
confidence: 99%
“…1.10.30.2) are multi-copper containing proteins that are widely distributed among fungi (23,25) but are also found in bacteria (1), insects (22) and plants (15). These enzymes are involved in lignin degradation (15) and their low substrate specificity allows them to oxidize a wide range of compounds, which makes them suitable for biotechnological and environmental applications (20). However, high amounts of the enzyme are needed for these applications, as well as to study and understand its properties and role in lignin biodegradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Lcc activity increased gradually after day 52 while MnP activity was completely suppressed. Lcc has been shown to be induced by aromatic compounds and metallic ions such as copper (Collins & Dobson, 1997;Saparrat et al, 2002;Scheel et al, 2000;Shutova et al, 2008;Soden & Dobson, 2001). Indeed, copper has been reported to be a strong laccase inducer in the white-rot fungi Pleurotus ostreatus (Palmier et al, 2000), Trametes pubescens (Galhaup & Haltrich, 2001;Galhaup et al, 2002), and T. versicolor (Collins & Dobson, 1997).…”
Section: Selective Induction Of Phenol-oxidizing Enzymementioning
confidence: 99%